2021
DOI: 10.21873/invivo.12660
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infections in Patients Undergoing Emergency Surgery: A Single-centre Experience

Abstract: Background/Aim: Surgical site infections (SSI) are associated with increased morbidity and mortality, and they occur more frequently during unplanned emergency surgical (ES) procedures rather than elective. Our aim was to determine the incidence of SSI within our ES cohort and to identify risk factors for SSI. Patients and Methods: Data from consecutive patients undergoing ES in a single institution during a 5-year period were prospectively collected and analyzed. Results: A total of 838 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Our study reported SSI as the most common POC (39%). However, these figures are higher than those reported in previous studies with patients similarly undergoing emergency surgery, such as Papadopoulos et al reporting SSI in 18.7% of patients [17], or Jatoliya et al with 26% [18]. This high frequency of SSI should be of concern because the ways to prevent them are widely known and accessible for application, and ideally, the trend should be that they occur less frequently, as found by Dencker et al in the USA [16].…”
Section: Discussionmentioning
confidence: 69%
“…Our study reported SSI as the most common POC (39%). However, these figures are higher than those reported in previous studies with patients similarly undergoing emergency surgery, such as Papadopoulos et al reporting SSI in 18.7% of patients [17], or Jatoliya et al with 26% [18]. This high frequency of SSI should be of concern because the ways to prevent them are widely known and accessible for application, and ideally, the trend should be that they occur less frequently, as found by Dencker et al in the USA [16].…”
Section: Discussionmentioning
confidence: 69%
“…These findings are similar to those provided in another report on the risk factors for SSIs in emergency surgery. 21 The average duration of hospital stay for the whole study population was 6.98 days while for those who developed a wound infection, it was 10.25 days. Hence the risk for SSIs increases with increase in duration of hospital stay.…”
Section: Discussionmentioning
confidence: 93%
“…Sumado a esto, existe evidencia previa que sugiere que la frecuencia de ISQ es dos veces mayor en los procedimientos de emergencia en comparación con las cirugías electivas [16]. Se ha sugerido que las cirugías de emergencia suelen presentar mayor grado de contaminación de las heridas y la realización de la intervención quirúrgica suele prolongarse por más tiempo [17], lo que podría explicar porque este tipo de cirugías son más susceptibles a desarrollar ISQ. Los resultados del presente estudio mostraron que las ISQ tanto en las cirugías ginecológicas como en las cirugías obstétricas, ocurrieron en pacientes con sobrepeso u obesidad.…”
Section: Discussionunclassified